The Effects of short light pulse at ZT21 on behavioral despair in old and young male wistar rats - Özcan, Elif Tunç. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The present study investigated potentially ameliorative and preventive effects of shortlight pulse exposure late at night (0400 h, ZT21) in both juvenile and adult rats. Animals weremaintained on a 12L/12D cycle (lights on at 0700 h) except for the days of light treatment in an insulated chamber. Light was provided by a 100W tungsten lamp, approximately 50 cmabove the cage housing the subjects. There were two control groups; the first one was treatedsimilarly except for photic stimulation and the second one was not put in the chamber but wasinstead taken directly from the vivarium for forced swimming tests. Our findings indicated that although light pulse exposure leads to a shorter duration of immobility and longerduration of swimming when employed before first forced swimming test (ZT21-B group), ityields no significant results. Furthermore, juvenile and adult rats differ from each other interms of the responses to the same stressors, namely the former displays more aggravated behavioral despair compared to the latter. However, the short light pulse exposure late at nighthas no ameliorative or preventive effects on behavioral despair as measured by the forced swimming test on either of the groups.
Keywords: Suprachiasmatic nucleus.; Circadian rhythms.; Biological rhythms.; Light -- Physiological effect.